THE INFLUENCE OF SERVICE INNOVATION AND SELF SERVICE TECHNOLOGY ON E-LOYALTY IN USING CASH BNI MANAGEMENT THROUGH E-SATISFACTION ON PT BANK NEGARA INDONESIA (PERSERO) Tbk. MEDAN BRANCH OFFICE - Mufida Sari; Endang Sulistya Rini; Syafrizal Helmi Situmorang (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
PT Bank Negara Indonesia (Persero) Tbk presents Cash Management financial services with various flagship features such as account information, transfer management, mass management, liquidity management and various other features which are expected to be able to answer the needs and provide ease of transactions and increase customer loyalty to PT Bank Negara Indonesia (Persero) Tbk. This study aims to analyze directly and indirectly the effect of Service Innovation and Self-Service Technology on E-loyalty in using Cash Management through E-Satisfaction at PT Bank Negara Indonesia (Persero) Tbk Medan Branch Office. This type of research is associative research. The types of data used are primary data and secondary data obtained from interview questionnaires and documentation studies. The population in this study were all BNI cash management customers at PT Bank Negara Indonesia Medan Main Branch Office, totaling 144 corporations/customers. Sampling in this study uses probability sampling technique. The criterion used is census sampling. Census sampling is a sampling technique by taking the entire total population to be used as a sample. The number of samples was 144 respondents. The data analysis method used is SEM-PLS. The results showed that the service innovation variable and the self service technology variable directly affect e-satisfaction and the service innovation variable and the self service technology variable directly affect e-loyalty, then the e-satisfaction variable directly affects e-loyalty, the service innovation variable indirectly has a significant effect on e-loaty through e-satisfaction, and the self service technology variable indirectly has a significant effect on loyalty through e-satisfaction.